Use of flow field-flow fractionation and single particle inductively coupled plasma mass spectrometry for size determination of selenium nanoparticles in a mixture. Issue 11 (11th February 2020) - Maknun, Luluil; Sumranjit, Jitapa; Siripinyanond, Atitaya
Abstract : Various analytical techniques have been used for size analysis of selenium nanoparticles (SeNPs). Abstract : Various analytical techniques have been used for size analysis of selenium nanoparticles (SeNPs). These include flow field-flow fractionation (FlFFF), single particle inductively coupled plasma mass spectrometry (SP-ICP-MS), dynamic light scattering (DLS) and transmission electron microscopy (TEM). For hydrodynamic diameter estimation, the FlFFF technique was used and the results were compared with those analyzed by DLS. For core diameter estimation, the results obtained from SP-ICP-MS were compared with those from TEM. Two types of FlFFF channel were employed, i.e., symmetrical FlFFF (Sy-FlFFF) and asymmetrical FlFFF (Asy-FlFFF). Considering the use of FlFFF, optimization was performed on a Sy-FlFFF channel to select the most appropriate carrier liquid and membrane in order to minimize problems due to particle membrane interaction. The use of FL-70 and 10 kDa RC provided an acceptable compromise peak quality and size accuracy for all samples of SeNPs which were coated by proteins (positively charged SeNPs) and sodium dodecyl sulfate (negatively charged SeNPs). FlFFF always yielded the lower estimate of the hydrodynamic size than DLS as a reference method. The results obtained by SP-ICP-MS were consistent with the TEM method for the core diameter estimation. The results from FlFFF and the DLS reference method were significantly different as confirmed by paired t -test analysis, while the results provided by SP-ICP-MS and the TEM reference method were not significantly different. Furthermore, consecutive size analysis by SP-ICP-MS for the fractions collected from FlFFF was proposed for sizing of SeNP mixtures. The combined technique helps to improve the size analysis in the complex samples and shows more advantages than using only SP-ICP-MS.